A Conservative Point Mutation in a Dynamic Antigen-binding Loop of Human Immunoglobulin λ6 Light Chain Promotes Pathologic Amyloid Formation. Issue 24 (3rd December 2021) - Peterle, Daniele; Klimtchuk, Elena S.; Wales, Thomas E.; Georgescauld, Florian; Connors, Lawreen H.; Engen, John R.; Gursky, Olga
Graphical abstract: Highlights: Drivers of Ig λ6 LC misfolding were identified by HDX MS and biochemical methods. CDR1 loop is the least protected part of the variable domain in λ6 LC class. N32T substitution in CDR1 increases protein dynamics and drives aggregation. Substitutions at several interacting sites contribute to AL amyloidosis. Substitution in a conserved position does not always predict AL. Abstract: Immunoglobulin light chain (LC) amyloidosis (AL) is a life-threatening human disease wherein free mono-clonal LCs deposit in vital organs. To determine what makes some LCs amyloidogenic, we explored patient-based amyloidogenic and non-amyloidogenic recombinant LCs from the λ6 subtype prevalent in AL. Hydrogen-deuterium exchange mass spectrometry, structural stability, proteolysis, and amyloid growth studies revealed that the antigen-binding CDR1 loop is the least protected part in the variable domain of λ6 LC, particularly in the AL variant. N32T substitution in CRD1 is identified as a driver of amyloid formation. Substitution N32T increased the amyloidogenic propensity of CDR1 loop, decreased its protection in the native structure, and accelerated amyloid growth in the context of other AL substitutions. The destabilizing effects of N32T propagated across the molecule increasing its dynamics in regions ∼30 Å away from the substitution site. Such striking long-range effects of a conservative point substitution in a dynamic surface loop may be relevant to Ig function. Comparison of patient-derived and engineered proteins showed that N32T interactions with other substitution sites must contribute to amyloidosis. The results suggest that CDR1 is critical in amyloid formation by other λ6 LCs.